Psychiatric co-morbidity in alcohol dependence: a cross-sectional study in a tertiary care setting. - Kattukulathil S, Kallivayalil RA, George R, Kazhungil F. (Kerala Journal of Psychiatry, 2015)
Background: Alcohol dependence is a very important public health issue in Kerala. Though alcohol dependence is demonstrated to be associated with psychiatric comorbidities, no attempts have been made to analyze the magnitude and pattern of comorbid psychiatric disorders in the state. Methods: We assessed 88 inpatients with ICD 10 diagnosis of alcohol dependence syndrome for the presence of comorbid psychiatric disorders, using ICD10 Diagnostic Criteria for Research, after two weeks of inpatient care. Patients with delirium tremens, alcohol-induced psychosis or organic illnesses were excluded. Results: 66.59% of our subjects had a comorbid psychiatric disorder. Bipolar affective disorder was the most common one (20.4%). Prevalences of other disorders were: unipolar depression (17%), phobia (9%), antisocial personality disorder (6.8%), generalized anxiety disorder (6.8%), schizophrenia (3.4%), obsessive compulsive disorder (1.1%) and delusional disorder (1.1%). Conclusion: Comorbid psychiatric disorders are highly prevalent in alcohol dependence. There is a need for further large-sample studies on the comorbidities and on integrated strategies for the identification and management of both alcohol dependence and comorbid psychiatric disorders.